NATURAL ANTIOXIDANTS AS DEFENSE SYSTEM AGAINST CANCER - Chahal, Anterpreet; Saini, Adesh K; Chhillar, Anil Kumar; Saini, Reena V (Asian Journal of Pharmaceutical and Clinical Research, 2018)
In living cells, the production of free radicals that comprise both reactive oxygen species (ROS) and reactive nitrogen species is highly regulated that help the cells to sustain redox homeostasis. Overproduction of ROS from mitochondrial electron transport chain leakage or excessive stimulation of xanthine oxidase and other oxidative enzymes leads to the uncontrolled production of free radicals leading to oxidative stress that can mediate damage to cell structures. This damage can be repaired by the antioxidant defense system. Antioxidants are capable of stabilizing, or deactivating, free radicals before they attack cellular components such as DNA, proteins, and lipids. The use of antioxidants in cancer prevention is a rapidly evolving research area where antioxidants scavenge free radicals and thus, indirectly help in the prevention of cancer. A wide range of antioxidants such as glutathione, N-acetylcysteine, coenzyme Q10, lycopene, flavonoids, and isoflavones when used in combination with chemotherapy and radiotherapy, result in the reduction of drug toxicity and enhanced efficacy of anticancer agents. This review aims at the use of these exogenous antioxidants as disease-oriented therapy and elucidating the relation of antioxidant enzymes with different types of cancers to overcome the harmful effects of cancer treatment.